Methimazole-induced hypothyroidism in rats ameliorates oxidative injury in experimental colitis - YEGEN, BERRAK (SOC ENDOCRINOLOGY, 2003)
Depression of metabolism by hypothyroidism decreases oxidant production and thus protects tissues against oxidant damage. Moreover, it is well-known that abnormal gut motility is a common manifestation in hypo/ hyperthyroidism. In this study, we aimed to investigate the putative beneficial effects of methimazole on oxidative injury and dysmotility in a rat colitis model. Methimazole (0(.)04%) was administered in drinking water starting 15 days prior to induction of colitis. Colitis was induced by intracolonic administration of trinitrobenzene sulfonic acid (30 mg/ml; 0(.)8 ml) in ethanol. Six days after the induction of colitis, the fecal output was measured and used as an index for colonic motility. All rats were decapitated on the seventh day. The distal colon was weighed and the mucosal lesions were scored. Colonic lipid peroxidation (LP) and glutathione (GSH) measurements were performed. The macroscopic score, the colonic wet weight and LP values of the euthyroid colitis group were found to be higher than those of the control group (P<0(.)05-0(.)001). All these parameters were reduced in the methimazole-treated colitis group (P<0(.)01-0(.)001). The decrease in colonic GSH levels in the colitis group was completely abolished in the methimazole-treated colitis rats (P<0(.)01). Induction of colitis increased the average fecal output compared with the control group (P<0(.)05) and methimazole in the colitis group exaggerated the fecal output (P<0(.)001). In conclusion, methimazole reduces colonic oxidative injury probably due to hypometabolism, which is associated with a decrease in the production of reactive oxygen intermediates and an increase in the response of antioxidant systems.
Keywords: INFLAMMATORY BOWEL-DISEASE; PERITONEAL-MACROPHAGES; LIPID-PEROXIDATION; DAMAGE; MICE; MODEL; FAILURE; TISSUES